2016
DOI: 10.1002/2015jc011486
|View full text |Cite
|
Sign up to set email alerts
|

Sources, fate, and pathways of Leeuwin Current water in the Indian Ocean and Great Australian Bight: A Lagrangian study in an eddy‐resolving ocean model

Abstract: The Leeuwin Current is the dominant circulation feature in the eastern Indian Ocean, transporting tropical and subtropical water southward. While it is known that the Leeuwin Current draws its water from a multitude of sources, existing Indian Ocean circulation schematics have never quantified the fluxes of tropical and subtropical source water flowing into the Leeuwin Current. This paper uses virtual Lagrangian particles to quantify the transport of these sources along the Leeuwin Current's mean pathway. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 49 publications
(129 reference statements)
3
14
0
Order By: Relevance
“…In a recent study, Ridgway and Godfrey () suggested that the monsoon wind setup sea levels on the Gulf of Carpentaria (GC) controlled the seasonality of the LC. In ozROMS, HLC accounted for ∼70% of the seasonal variance of LC, SAC and ZC in agreement with Yit Sen Bull and van Sebille (). A small secondary maximum in transport occurred in January (summer) for HLC, LC, and SAC.…”
Section: Discussion and Summarysupporting
confidence: 85%
See 1 more Smart Citation
“…In a recent study, Ridgway and Godfrey () suggested that the monsoon wind setup sea levels on the Gulf of Carpentaria (GC) controlled the seasonality of the LC. In ozROMS, HLC accounted for ∼70% of the seasonal variance of LC, SAC and ZC in agreement with Yit Sen Bull and van Sebille (). A small secondary maximum in transport occurred in January (summer) for HLC, LC, and SAC.…”
Section: Discussion and Summarysupporting
confidence: 85%
“…Magnitudes of the transport, temporal, and spatial variability of the major surface boundary currents (e.g., LC, SAC, EAC, and FC) are generally known but details of inflows into these surface current systems and the transport and variability of the subsurface current systems are largely uncertain. It is known that both the LC and EAC strengthen as they flow southward along the western and eastern shelf slopes of Australia with inflows from the subtropical branches of SICC and SEC, respectively (Domingues et al, ; Ridgway et al, ), however a recent study by Yit Sen Bull and van Sebille () suggested that tropical sources account for between 60 and 78% of the LC transport.…”
Section: Introductionmentioning
confidence: 99%
“…Transport of international plastic pollutants to the area is facilitated through entrainment of Indian Ocean surface waters and the ITF, which extends into the Holloway and then Leeuwin Current, capable of transporting water down the coast from Asia (Meyers et al, 1995;Pattiaratchi and Woo, 2009). ITF waters are hereby modeled to make up the highest proportion of water transported in the LC (Yit Sen Bull and van Sebille, 2016). Importantly, the three countries with the highest estimated influx of mismanaged plastic waste to the ocean-namely China, Indonesia and the Philippines-are directly connected to Western Australia by these surface currents (Jambeck et al, 2015).…”
Section: Leeuwin Current In the Offshorementioning
confidence: 99%
“…The LC is driven by an alongshore geopotential gradient created by warm, nutrient-poor Pacific Ocean waters spilling into the Indian Ocean with the Indonesian Through-flow (ITF) (Pearce and Phillips, 1988;Fieux et al, 2005). While most of the ITF contributes to the westward flowing Indian Ocean Equatorial current, some of it flows into the Holloway current along the North West shelf of Australia and extends further south where it contributes to the LC (Pearce and Phillips, 1988;Yit Sen Bull and van Sebille, 2016). Seasonal variability of the LC creates strongest transport during the austral winter months, as opposing winds weaken (Godfrey and Ridgway, 1985;Feng et al, 2003).…”
Section: Leeuwin Current In the Offshorementioning
confidence: 99%
“…Feng et al (2003) studied the seasonal cycle of the LC at 328S; they found that the LC meridional transport attained a maximum during JuneJuly (5 Sv) and that its annual mean over the entire record was 3.4 Sv. More recently, Yit Sen Bull and van Sebille (2016) used Lagrangian virtual floats in their eddy-revolving ocean general circulation model (OGCM) to find annual-mean LC transport values similar to Feng et al's (2003).…”
mentioning
confidence: 99%